Peran Continuous Auditing dan Skeptisme Profesional dalam Meningkatkan Sistem Pengendalian Intern Pemerintah melalui Pemanfaatan Teknologi Informasi : (Studi pada Inspektorat Kabupaten Bone Bolango) - Sutya Rauf; Usman Usman; Victorson Taruh (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to examine the effect of continuous auditing and auditor skepticism on the implementation of the Government Internal Control System (SPIP) supported by information technology in the Government of Bone Bolango Regency. A quantitative approach was applied using the Partial Least Squares (PLS) method to test the hypotheses, with data collected through questionnaires distributed to 74 auditors and financial staff of the Regency Inspectorate as respondents. The findings indicate that continuous auditing has a positive and significant effect on SPIP (t-statistic 2.501; p-value 0.024), and auditor skepticism also shows a positive and significant influence (t-statistic 6.454; p-value 0.000). Information technology further enhances audit effectiveness and promotes transparency and accountability in regional financial management. These results confirm that strengthening SPIP depends on the consistent implementation of continuous auditing, auditors’ professional skepticism, and the optimal use of technology. Therefore, the local government, particularly the Inspectorate of Bone Bolango Regency, should enhance staff competencies and maximize the utilization of information technology to improve supervisory effectiveness, reduce the risk of violations, and increase public trust in regional financial governance.